Impact of socioeconomic change and hygiene sanitation during pandemic covid-19 towards stunting: an analytical study in coastal area - Diyah Arini; Dwi Ernawati; Dewinta Hayudanti; Arie Dwi Alristina (International Journal of Public Health Science (IJPHS), 2022)
The global COVID-19 pandemic has raised the risk of malnutrition in children, particularly those under the age of five, including stunting. Stunting is common in low-income regions, when families cannot afford nutritious meals. Certain types of food may not be available or cheap for some families during the COVID-19 epidemic. Stunting may become more common as a result of changes in family socioeconomic circumstances, personal cleanliness, and environmental sanitation during the pandemic. This study is to determine the effect of socioeconomic factors and hygiene sanitation during COVID-19 pandemic on the incidence of stunting in coastal areas. This type of research was analytical survey with cross sectional approach. The total sample was 3886 families who had children had toddlers aged 0-59 months in the coastal areas in Surabaya City, Indonesia. The instrument in this study was filling out a questionnaire using Google Form on socioeconomic and hygiene sanitation factors to determine the incidence of stunting. Socioeconomic determinant which impacted stunting was family income. While whole hygiene and sanitation determinants have significant impact to stunting by chi square test (pvalue=0,002). Highest odds ratio from logistic regression was 15,4 higher between other socioeconomic determinants. Whereas the hygiene and sanitation factor which has the highest impact was hand-washing habit with odds ratio 75,3. Hand-washing habit has significance impact which was proved by chi square test (pvalue=0,000). Low family income, hand-washing habits, clean water sources, sewer access, waste management, and healthy latrine have significant impact to malnutrition, especially stunting.